Differences and similarities between Journal Impact Factor and CiteScore - Fernandez-Llimos F (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Two major journal-based metrics are in competition: the Journal Impact Factor and CiteScore. Although these two metrics are based on similar principles of measuring the impact by citations, some differences between them exist. Years used to calculate the metric, access to computing data, and number of journals covered are some of these differences. One of the most relevant differences for pharmacy journals is the recognition in CiteScore of Pharmacy as an independent Subject Area, whereas it appears to have merged with pharmacology in the Journal Citation Reports. The immediate consequence of this differentiation is that pharmacy journals remain in the third and fourth quartiles in the Journal Impact Factor distribution, while a true quartile distribution exists in CiteScore.